Reviewing the Efficiency of Field and Experimentally Utilized Vaccine Regimens Against Infectious Bronchitis Virus in Egypt (2000-2021) - Mahmoud, Ali M.; Hamouda, Esraa E.; ElBakrey, Reham M.; Eid, Amal A.M. (Journal of Advanced Veterinary Research, 2024)
Infectious bronchitis is an acute, highly contagious upper respiratory tract disease in chickens. Reduced egg production and quality are common, and nephritis can be caused by some strains. Attenuated live, killed, and recently recombinant vaccines are available, but different antigenic types of the avian coronavirus causing the disease do not cross-protect, complicating control efforts. Vaccination regimens against IBV often induce insufficient levels of cross-protection field challenge. In the current work, we reviewed the data outcomes of the field and experimental vaccine efficacy in view of the available literature during 2000–2021 in Egypt, as well as the geo-epidemiological distribution of the virus infection among different Egyptian provinces within the time frame of the study. Among seventeen provinces, Sharkia came in at the top of the list, with the highest IBV incidence in field-vaccinated flocks that received a single classic live vaccine. However, experimentally, the protective percentage for the same vaccine regime extremely varied from 50% to almost 100%. The introduction of variants with classics proved lower incidence in the field IBV isolates and higher protection in experimental trials, which varied according to the variant vaccine used and the strain of the challenge virus. In conclusion, the vaccination efficacy against IBV is a crucial issue, and we must keep in mind proper vaccine handling, application, and the maximal use of one classic beside one variant as a protectotype along the Egyptian farms to avoid the evolution of more variants.